Visiting Critical Exploration in the Classroom (LEARNing Landscapes, 2021)
In this commentary, summarized from a recent interview, the author reminisces about a career dedicated to critical exploration in the classroom. She discusses the formation of the Moon Group, a group of teachers who met over a period of 25 years to study the behaviour of the moon. Duckworth later describes an exercise in which her students experimented with the positioning of a small mirror in the classroom in order to be able to predict where to place it on a wall so one student can see another in a different part of the room. In another exercise, she had university students observe the learning of children by having them solve spatial problems without any advice or prompts from an adult. She concludes by providing guidance for classroom teachers, emphasizing the importance of making sure, “what you want them to learn is worth learning about.”
Keywords: critical exploration; Piaget; Inhelder; innate learning of children; The Moon Group; The Mirror Exercise; Freirean approach; Elementary Science Study Project